Visual Disturbances in Young Patients with Cervical Spine Osteochondrosis Working at the Computer - Jurabekova A.T.; Eshimova Sh.K.; Bekturdiev Sh.S. (Genius Journals, 2023)
The American professor Mitchell D. once called osteochondrosis of the spine -"the demon in the back". Modern man due to urbanization suffers from deteriorating environmental conditions from poor diet and quality of nutrition, sedentary lifestyle, all this affects changes in the structure of the spine.
Keywords: Visual impairment; young adults; cervical osteochondrosis; computer